2011
DOI: 10.1111/j.1651-2227.2011.02478.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia in feverish children presenting to the emergency department: a retrospective study and literature review

Abstract: Overall bacteremia rate is currently <0.5% in well-appearing children aged 3-36 months with FWS attending the PED in areas with PCV-7 widespread vaccination and is sufficiently low to preclude laboratory testing in favour of close follow-up. Further research is needed to evaluate a more conservative approach in infants 2-3 months of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
2
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 28 publications
0
36
2
3
Order By: Relevance
“…14,29 Studies from the United States, Spain, and Italy have reported similar findings even in settings with moderate PCV7 coverage. [37][38][39][40][41] We also observed a trend toward an increase in the proportion of meningitis in infants with IPD after the introduction of PCV7. Poehling et al 9 reported a 15% proportion of meningitis in young infants; however, Ladhani et al 10 reported a higher proportion of meningitis (37%), which is similar to our study.…”
Section: Figurementioning
confidence: 49%
“…14,29 Studies from the United States, Spain, and Italy have reported similar findings even in settings with moderate PCV7 coverage. [37][38][39][40][41] We also observed a trend toward an increase in the proportion of meningitis in infants with IPD after the introduction of PCV7. Poehling et al 9 reported a 15% proportion of meningitis in young infants; however, Ladhani et al 10 reported a higher proportion of meningitis (37%), which is similar to our study.…”
Section: Figurementioning
confidence: 49%
“…The proportion of occult bacteremia is variable, and for children less than 3 years of age, it was estimated to be 3-10% in the pre-Hemophilus influenzae B (HiB) vaccine era. This figure has dropped after the introduction of the HiB vaccination and is currently 0.5% after the worldwide adoption of this vaccination program [10]. The mortality rate associated with bacteremia may be as high as 30% [11].…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate associated with bacteremia may be as high as 30% [11]. The clinical management of children older than 3 months of age, who present in the PED with fever, is still controversial [10,12]. There is great heterogeneity in the evaluation and the management practices of this group of patients, including the need for a complete blood count (CBC), measurement of C-reactive protein (CRP) and blood culture (BC) [2][3][4]6,7,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ante una BO por este microorganismo, existe de 1% a 5,8% de riesgo de meningitis, de 6% a 10% de otras infecciones localizadas, 0,8% de letalidad; entre un 70% y un 87,5% puede autolimitarse sin mediar tratamiento. 3,16,[37][38][39][40][41][42][43][44] Aproximadamente, 0,02% de los pacientes de 3 a 36 meses con FSF > 39 °C tienen BO por Nm. La presencia de petequias o lesiones purpúricas fuera del área de Valsalva constituyen un signo de alerta.…”
Section: Fiebre Sin Foco Evidente De Infección En Niños De 3 a 36 Mesunclassified